Degradation of Orange G Induced by Fe(III)-Oxalate Complex in Irradiated Solution - Ou, Xiaoxia; Zhang, Fengjie; Wang, Chong (Asian Journal of Chemistry, 2012)
The photolysis of orange G in a Fe(III)-oxalate system was investigated under simulated sunlight. Orange G could be effectively photodegraded by the Fe(III)-oxalate system as a result of the formation of the highly oxidizing hydroxyl radical, •OH. Orange G degradation followed the first-order kinetics and depended significantly on the initial concentration of Fe (III), oxalic acid and orange G, showing that the photolysis rate increased with increasing iron and oxalic acid concentration and decreased with increasing orange G concentration. The degradation rate constant of orange G changed from 0.0018 min-1 to 0.0183 min-1 corresponding to the dosage of oxalic acid ranged from 0 to 150 μM under conditions of pH = 4.0, Fe(III) = 20 μM. The interaction of Fe(III) with oxalic acid was characterized using UV-Vis and Fourier transform infrared (FTIR) spectroscopy, indicating that the hydrogen ions on the carboxyl groups were exchanged for Fe(III) ions.